Transforming Village Development: Strategies for Boosting Community Involvement - Agus Hariyanto; Dwi Putranto Riau; M. Nur Affandi (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2025)
This study examines community participation in village development planning in Nusa Maju Village, Belitang III District, South Sumatra. Employing a qualitative descriptive approach, the research explores the extent of participation across four stages: planning, implementation, evaluation, and utilization. It also identifies key factors influencing engagement, such as socio-economic conditions, government policies, and cultural norms. The findings reveal high levels of participation during the planning and implementation stages, but limited involvement in evaluation and monitoring. The study emphasizes the importance of government transparency, inclusive decision- making, and community empowerment in fostering greater participation. It contributes to the broader understanding of participatory development and offers recommendations for enhancing community engagement in future village development initiatives.